Tumores cerebrales en pacientes menores de 3 años: 10 años de experiencia - Saravia Toledo, Alejandro; Ortiz Vica, A. Emanuel; E. Espil, Pablo; G. Musso, Alejandro; Jaikin, Mario S. (Revista Argentina de Neurocirugía, 2020)
Introduction: The first three years of life are critical for the central nervous system (CNS) development. A tumor in this location at this stage will be associated with severe impairment of the quality of life and high mortality. The objective of the paper is to analyze the evolution and treatment of these patients. Material and methods: The records of all the patients under 3 years of age who were operated for intracranial brain tumors at our institution from March 2009 to January 2020 were retrospectively reviewed. Patients were divided into three groups depending on their age at onset: under 1 year of age (group 1), between 13-24 months (group 2), and between 25-35 months (group 3). Results: We included 71 patients (36 male and 35 female). 42 patients (59%) presented with an increase of intracranial pressure at the onset, followed by gait disturbance in 13 (18%). 46 patients (65%) suffered hydrocephalus, of whom 20 were post-resection. The predominance of supratentorial localization was observed in group 1 (69%) and 2 (58%), and infratentorial localization in group 3 (86%). Total resection of the tumor was accomplished in 18 patients (25%), subtotal in 6 (11%), partial in 38 (54%), and biopsy in 7 (10%). 27 patients (38%) required re-intervention. Of these, 19 (70%) corresponded to group 1. The principal histological diagnoses were astrocytoma (20), medulloblastoma (12), choroid plexus papilloma (9), anaplastic ependymoma (8), atypical teratoid rhabdoid tumor (8), and others (14). The quality of life analysis showed 23 patients (32%) with normal development and 15 (21%) with severe psychomotor retardation. 5-years mortality was 38% and 10-years mortality was 50%. Conclusion: CNS tumors in children younger than 3 years are difficult to handle and have a guarded prognosis. Surgery, along with chemotherapy, is very important to treat these patients.